P413 Withdrawal versus continuation of thiopurine in vedolizumab-treated patients with Ulcerative Colitis (VIEWS): a multi-centre randomised controlled trial. (30th January 2023) - Pudipeddi, A; Paramsothy, S; Kariyawasam, V; Paramsothy, R; Ghaly, S; Haifer, C; An, Y K; Begun, J; Connor, S; Corte, C; Ward, M; De Cruz, P; et al.
Abstract: Background: The benefit of continuing thiopurine in ulcerative colitis (UC) responders to vedolizumab (VED) is unclear. We aimed to determine the effect of thiopurine withdrawal in VED-treated UC patients on combination therapy. Methods: This prospective multi-centre, single-blind, randomised controlled trial recruited UC patients on VED 300mg IV every 8 weeks and a thiopurine for ≥6 months. Patients in steroid-free clinical remission (partial Mayo score[pMS]≤2, no subscore>1) and endoscopic remission/improvement (Mayo endoscopic subscore[MES]≤1) were randomised 2:1 to withdraw or continue thiopurine. Primary outcome was comparing week 48 VED trough levels. Secondary outcomes were disease relapse (pMS≥3 and faecal calprotectin>150μg/g or increase in MES≥1 from baseline), centrally-read endoscopic remission (MES=0), histologic remission (Nancy index=0), histo-endoscopic remission, faecal calprotectin (remission<150μg/g) and adverse events. Results: Sixty-two consecutive patients (58% males, median follow-up 23.0 months) were randomised to withdraw (n=42) or continue (n=20) thiopurine. Randomisation was balanced. Complete data was available for 58 patients. There was a non-significant trend toward increased disease relapse in the withdrawal group ( P =0.12, Fig. 1). In the withdrawal group, baseline histologic activity significantly increased disease relapse (HR:5.8, 95%CI:1.6-20.8, P =0.007, Fig. 2). There was a trend towards higher relapse rates in the withdrawal versus continue groups for bio-exposed patients (50.0% [6/12] vs 0.0% [0/4], P =0.07) but not bio-naïve patients (20.0% [6/30] vs 12.5% [2/16], P =0.52). At week 48, the continue group had significantly higher histologic remission (OR:4.6, 95%CI:1.1-18.9, P =0.03) and histo-endoscopic remission rates (OR:4.6, 95%CI:1.3-16.1, P =0.01, Fig. 3) versus the withdrawal group, but similar endoscopic remission rates ( P =0.09, Fig. 3). Faecal calprotectin remission was significantly higher in the continue (94% [16/17]) versus withdrawal group (70% [28/40], P =0.047) with mean calprotectin 44.5μg/g±SD56.2 vs 209.6μg/g±SD344.2 ( P =0.003) respectively. On multivariate analysis, histologic activity at baseline (HR:5.3, 95%CI:1.1-26.2, P =0.04) predicted disease relapse. Week 48 median VED levels were 15.9µg/mL (IQR:10.1-22.7) in the withdrawal group versus 14.7µg/mL (IQR:12.1-18.7) in the continue group ( P =0.43). No patients had anti-VED antibodies. There was no significant difference in adverse events between groups. Conclusion: Although thiopurine withdrawal did not affect VED trough level, it increased calprotectin, histologic and histo-endoscopic activity in UC. In patients with histological activity despite deep remission, thiopurine withdrawal significantly increased the risk of disease relapse.